Human resource management (HRM) practices and employee performance in privatized companies: The moderating role of organizational politics - Kashoob A.; Jais J. (Science and Engineering Research Support Society, 2023)
Privatization is advocated as an economic reform policy and efficient alternative for public organizations to improve quality and accountability of services in public sector. Privatized companies need to emphasize on HRM in order to positively enhance employee performance. This paper examines the association between selected HRM practices and employee performance with emphasis on the moderating impact of organizational politics in privatized companies. This research assumes that privatized companies might have a favorable organizational politics compared to public companies which positively enhances the employee performance. Through a review and synthesis of extant literature, this paper tends to develop an employee performance model based on selected HRM practices and interaction of these HRM practices and organizational politics. 2019 SERSC.